2004
DOI: 10.1023/b:nere.0000018848.58358.95
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of 3 –5  Exonuclease Activity in Rat Brain Neurons and Its Role in Template-Driven Extension of 3 -Mismatched Primers by DNA-Polymerase   in Aging Neurons

Abstract: A three-step reaction strategy has been developed to examine the mechanism of extension of a mismatched primer in an oligoduplex substrate by rat neuronal extracts and DNA polymerase beta. The results revealed that in the case of duplexes with a mismatch at 3'-end of primer, significant extension by DNA polymerase beta has taken place only after the removal of the mismatched base, thus indicating the presence of a proof reading 3'-5' exonuclease activity in neuronal extracts of all ages. A closer examination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…depurinated plasmid DNA, uracil or tetrahydrofuran containing 5′-3′ oligonucleotides) that the activity of this repair enzyme is considerably variable in human tissues (i.e., brain, lymphocytes). Based upon previous work in the rat brain (Krishna et al, 2004), we reasoned that tissues contain different amounts of 3′-5′ exonucleases, and this enzyme could readily degrade the more traditional APE substrates leading to an incorrect assessment of cellular APE activity. This could also explain why APE activity is variable in the brain of ALS subjects (Kisby et al, 1997) and there is an observed discrepancy for the age-associated changes in mitochondrial or nuclear APE activity (Chen et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…depurinated plasmid DNA, uracil or tetrahydrofuran containing 5′-3′ oligonucleotides) that the activity of this repair enzyme is considerably variable in human tissues (i.e., brain, lymphocytes). Based upon previous work in the rat brain (Krishna et al, 2004), we reasoned that tissues contain different amounts of 3′-5′ exonucleases, and this enzyme could readily degrade the more traditional APE substrates leading to an incorrect assessment of cellular APE activity. This could also explain why APE activity is variable in the brain of ALS subjects (Kisby et al, 1997) and there is an observed discrepancy for the age-associated changes in mitochondrial or nuclear APE activity (Chen et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The softwares used are available over World Wide Web. 5 0 Deoxyribose Phosphate (dRP) Lyase Activity Assay dRP lyase assay was done according to the procedure of Prasad et al 1998 [38] and in brief, the methodology involves following steps: 3 0 End Labeling Controlled 3 0 end labeling of 10 picomole of 21-mer oligodeoxyribonucleotide containing uracil at 8th position from 5 0 end was carried out with 50 lCi of a-32 P-dCTP by terminal deoxynucleotidyl transferase in buffer containing 100 mM potassium cacodylate pH 7.2, 2 mM CoCl 2 , and 2 units of terminal transferase for 10 min such that only one labeled nucleotide was added at the 3 0 end [39].…”
Section: In Silico Analysismentioning
confidence: 99%